Biopesticidal potential of insect derived chitosan for crop protection - Arasu, A; Srinivasan, G; Shanthi, M; Murugan, M; Saravanan, S; Sivaraman, A (Plant Science Today, 2025)
In recent years, increasing environmental concerns and regulatory restrictions on conventional chemical pesticides have driven the demand for safer, biodegradable and eco-friendly alternatives. Among these, chitosan, a natural polysaccharide derived from the deacetylation of chitin, has gained significant attention due to its broad spectrum antimicrobial, antifungal, antiviral, insecticidal and plant defense inducing properties. Traditionally, chitosan is sourced from marine crustaceans like shrimps and crabs. However, emerging studies have highlighted the untapped potential of insect-based chitosan extracted from species such as Hermetia illicens (Black soldier fly), Bombyx mori (Silkworm) and Tenebrio molitor (Mealworm) as promising biocontrol agents in agriculture. Compared to marine sources, insect derived chitosan offers more advantages which includes all season availability, rapid biomass generation, lower allergenicity and reduced ecological footprints. Insect derived chitosan often shows higher deacetylation and lower molecular weight, enhancing solubility and biological activity against pests and diseases. This review explores the potential of chitosan derived from various insect sources, focusing on its application against a wide range of agricultural pests and phytopathogens. It synthesizes current findings on physicochemical properties, formulation approaches (e.g. nanoparticles, coatings, foliar sprays) and elucidates the mechanisms through which insect-based chitosan disrupts pest physiology, inhibits pathogen growth and elicits systemic resistance in plants. Furthermore, it evaluates the advantages and limitations of insect-sourced chitosan over traditional sources and highlights knowledge gaps, regulatory challenges and future directions for field-level adoption in Integrated Pest Management (IPM) systems.